Analisis Perbandingan Metode Pracetak Dan Metode Konvensional Dalam Pembangunan Rumah Susun 4 Lantai Di Surabaya - Fikri, Mohammad Rijal; Sutriono, Bantot (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2025)
This study compares the structural performance of precast construction and conventional construction methods in a 4-stories flats building in Surabaya. The results show clear differences in the forces acting on the structural elements. Precast elements have shear forces that are 21% lower than those in the conventional method and moments that are 25% lower than those in the conventional method, indicating different responses to lateral loads. Although both methods use similar reinforcement designs, precast elements need extra reinforcement for lifting during installation. The drift analysis on the second floor also shows differences: the precast structure has 21% less than those in the conventional method drift the x-direction and 21% less than those in the conventional method the y-direction due to changes in overall stiffness.